Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Characterization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian (Welding in the World)

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Material-specific prediction of the optimal joinig parameters for the screw blind rivet joining process - Moritzer, Elmar; Held, Christian; Hillemeyer, J. (Welding in the World)

Influence of material degradation on weld seam quality in hot gas butt welding of polyamides - Bialaschik, Max; Schöppner, Volker; Albrecht, Mirko; Gehde, Michael (Welding in the World)
The joining of plastics is required because component geometries are severely restricted in conventional manufacturing processes such as injection molding or extrusion. In addition to established processes such as hot plate welding, infrared welding, or vibration welding, hot gas butt welding is becoming more and more important industrially due to its advantages. The main benefits are the contactless heating process, the suitability for glass fiber reinforced, and high-temperature plastics as well as complex component geometries. However, various degradation phenomena can occur during the heating process used for economic reasons, due to the presence of oxygen in the air and to the high gas temperatures. In addition, the current patent situation suggests that welding with an oxidizing gas is not permissible depending on the material. On the other hand, however, there is experience from extrusion welding, with which long-term resistant weld seams can be produced using air. Investigations have shown that the same weld seam properties can be achieved with polypropylene using either air or nitrogen as the process gas. Experimental investigations have now been carried out on the suitability of different gases with regard to the weld seam quality when welding polyamides, which are generally regarded as more prone to oxidation. The results show that weld strengths are higher when nitrogen is used as process gas. However, equal weld strengths can be achieved with air and nitrogen when the material contains heat stabilizers.

Refill friction stir spot and resistance spot welding of aluminium joints with large total sheet thicknesses (III-1965-19) - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Refill friction stir spot welding (RFSSW) is a highly flexible and promising solid-state joining method for aluminium alloys. Alternatively, resistance spot welding (RSW) can be stated as an appropriate joining method which can be automated and used within a high-volume production due to short process times. Both processes do not need any additional elements and a flat surface on both sides of the joints can be realised. In order to meet the modern requirements for crash safety and structural stiffness, thermal and mechanical joining methods are mainly combined by using single-component epoxy resin adhesives. Due to an insufficient knowledge about the application of both thermal joining methods for the abovementioned material combinations combined with additional adhesives, deeper investigations were done regarding the interactions of the polymers and the joining processes. Starting with a brief presentation of the boundary conditions of the investigations and the refill friction stir spot welding and resistance spot welding of high-strength aluminium alloys with sheet thicknesses bigger than 5.8 mm, the paper introduces the process-related joint properties of friction-based and resistance-based welded joints. Afterwards, the paper discusses the influences of the process parameter on the metallographic joint formation and load-bearing capacities for a selected two-sheet and four-sheet material combination. When combining the spot welding technologies with adhesives, the process parameters of the RFSSW process have to be adapted for the two-sheet combination by adding a squeeze-out step, while for RSW, just the preholding time has to be increased. Different challenges for both joining methods are shown. For RFSSW, the gap formation has to be considered when welding big total sheet thicknesses, while for RSW, the shape of the weld nugget is more important for an appropriate joint performance. Additionally, process optimisations for less adhesive incineration will be discussed for both joining processes, and the influences of the adhesive on the joint formation will be addressed with the help of load-bearing capacity evaluations. The paper closes with specific recommendations for the realisation of refill friction stir and resistance spot-welded joints with and without adhesive in the field of Al joints with big total sheet thicknesses which meet the quality demands and an outlook for further research steps will be given.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Process characteristics and influences of production-related disturbances in resistance element welding of hybrid materials with steel cover sheets and polymer core - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Adhesive bonding of FDM-manufactured parts made of ULTEM 9085 considering surface treatment, surface structure, and joint design - Bürenhaus, Franziska Isabelle; Moritzer, Elmar; Hirsch, André (Welding in the World)

Joining of high strength aluminum alloys by refill friction stir spot welding (III-1854-18) - Schmal, Christopher; Meschut, Gerson; Buhl, Nico (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Mechanical properties of repair welded joints for automobile body structures - Ditter, Jan; Wünsche, Marc; Meschut, Gerson; Wibbeke, Tim Michael (Welding in the World)

Innovative joining technology for multi-material applications with high manganese steels in lightweight car body structures - Ivanjko, Martin; Meschut, Gerson (Welding in the World)

Factors Influencing the Fiber Orientation in Welding of Fiber-Reinforced Thermoplastics - Schöppner, Volker; Fiebig, J. (Welding in the World)

Influence of Fiber Orientation and Weld Position in Welding Injection-Molded Fiber-Reinforced Thermoplastics - Schöppner, Volker; Fiebig, I. (Welding in the World)

Application of self-piercing nuts during hot forming of 22MNB5 - Meyer, Sebastian; Meschut, Gerson; Vogt, Hendrik; Behrens, Bernd-Arno; Hübner, Sven; Neumann, André (Welding in the World)

Bonding of wood-plastic composites (WPC)—material and surface modification for special applications - Moritzer, Elmar; Hopp, Matthias (Welding in the World)

Process characteristics and load-bearing capacities of joints welded with elements for the application in multi-material design - Meschut, Gerson; Schmal, Christopher; Olfermann, Thomas (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Self-locking self-pierce riveting: a new self-pierce riveting technology for multi-material applications in lightweight car body structures - Sartisson, Vadim; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Combining a high-speed mechanical joining technique with the attachment of functional elements in automotive structures - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Flow drill screwing of fibre-reinforced plastic-metal composites without a pilot hole - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

The Influence of Welding Processes on the Weld Strength of Flame-Retardant Materials - Schöppner, Volker; Evers, F.; Lakemeyer, P. (Welding in the World)

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Affect of Atmospheric Pressure Plasma Pre-Treatment and Aging Conditions on the Surface of Thermoplastics - Moritzer, Elmar; Budde, C.; Leister, C. (Welding in the World)

The use of radiation-cured adhesives on adhesive stud assembly process - Meschut, Gerson; Süllentrop, Sebastian (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Influence of the dosing and mixing technology on the property profile of two-component adhesives - Meschut, Gerson; Hahn, O.; Teutenberg, Dominik; Ernstberger, L. (Welding in the World)

Influence of the curing process on joint strength of a toughened heat-curing adhesive - Meschut, Gerson; Hahn, O.; Teutenberg, Dominik (Welding in the World)

Innovative joining technologies for multi-material structures - Meschut, G.; Hahn, O.; Janzen, V.; Olfermann, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Predicting production influences on adhesively bonded joints subjected to cyclic load - Teutenberg, Dominik; Hahn, Ortwin (Welding in the World)